PENYIMPANGAN PELAKSANAAN PERLINDUNGAN HUKUM TERHADAP TENAGA KERJA OUTSOURCING DARI KONTEKS UNDANG-UNDANG NOMOR 13 TAHUN 2003 - Totok Tumangkar (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2011)
To provide employment protection for a specific time or outsourcing manpower contracts, the provisions of Article 6 of Law No. 13 of 2003 on Manpower stated: "Every worker / laborer is entitled to equal treatment without discrimination from employers". Under Article 6 of Law No. 13 of 2003, then every worker is entitled to workers' equal treatment without distinction of businessmen, just how entrepreneurs in realizing, working period appreciation, money for substituting health benefits and money for substituting annual leave. Problems of labor protection in the implementation are still far from expectations. This is evidenced in employment practices; there are still things that are not in accordance with stipulated in the Employment Act. In which a lot of employers are still to make their own rules for corporate interests regardless of what the rights of its workforce. It can be concluded that the right of labor to labor rights, was not specifically stated in the works agreement. Time for outsourcing work agreement was no later than 2 years. The will to earn a decent wage was far from the expectations of the outsourced workers, while the workers still have not necessarily paid a fair wage. The implementation of legal protection for outsourcing labor is employment conditions that are structural in nature. The volatile strategic environments, globalization, needs (human needs) which always increased as well, the role and function of the means of industrial relations that must be optimized. The things that can be done to overcome these obstacles is the implementation of the labor inspection system which is adopted " " or also called by an. This integrated system is based on the Regulation of Manpower Minister No. ERT. 3/MEN/1984, integration is carried out covering education employment supervision, field operations and management.